Does fire always accelerate shrub expansion in Arctic tundra? Examining a novel grass-dominated successional trajectory on the Seward Peninsula - Teresa N. Hollingsworth; Amy L. Breen; Rebecca E. Hewitt; Michelle C. Mack (Arctic, Antarctic, and Alpine Research, 2021)
Over the last century in the circumpolar north, notable terrestrial ecosystem changes include shrub expansion and an intensifying wildfire regime. Shrub invasion into tundra may be further accelerated by wildfire disturbance, which creates opportunities for establishment where recruitment is otherwise rare. The Seward Peninsula currently experiences more frequent and larger fires than other tundra regions in Alaska. There are areas of overlapping burn scars dating back to the 1950s. Using a chronosequence approach, we examined vegetation and ecosystem dynamics in tussock tundra. Increasing burn severity and fire frequency corresponded with an increase in grass cover and a decrease in shrub basal area. We used multivariate ordination analysis to create a single integrator variable of fire effect that accounted for time after fire, burn severity, and number of times burned. This fire effect was significantly associated with decreases in soil organic layer thickness and overall plant biomass. Unlike previous studies in Arctic Alaska tundra, we found that increases in fire frequency and severity did not increase shrub cover and biomass. Instead, intensifying fire disturbance, and particularly repeat fires, led to grass dominance. Our findings support the hypothesis that intensifying tundra fire regimes initiate alternative post-fire trajectories that are not shrub dominated and that are structurally and functionally quite different from sedge or shrub-dominated tundra.